What Do Parties Want? An Analysis of Programmatic Social Policy Aims in Austria, Germany, and the Netherlands - Silke van Dyk; Martin Seeleib-Kaiser; Martin Roggenkamp (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2005)
Comparative welfare state research has argued for some time that it makes a difference in regards to the specific welfare state design whether Social Democrats or Christian Democrats are in government. The theory is based on the fact that historically the social policy aims of Social Democrats and Christian Democrats have differed. But can these policy differences still be assumed after almost three decades, which have been characterised by a discourse about necessary welfare state retrenchment, adaptation, and modification? More specifically, in which way have 'new' ideas altered the social and economic policy concepts? We hypothesise that the differences among the two welfare state parties in formerly conservative welfare states have largely faded away. Moreover, we argue that, in the meantime Social Democrats as well as Christian Democrats pursue a more or less common liberal-communitarian approach in welfare state policies in these countries. Our study is based on an in-depth analysis of programmatic approaches by Social Democrats and Christian Democrats in Austria, Germany, and the Netherlands since 1975. Based on Christian-Democratic and Social Democratic ideal types, we pay special attention to the development of employment, social security, and family policies. – – Ein grundlegender Befund der vergleichenden Wohlfahrtsstaatsforschung bestand lange Zeit darin, dass die spezifische Ausgestaltung von Wohlfahrtsstaaten in hohem Maße dadurch bestimmt wird, ob diese von sozialdemokratischen oder christdemokratischen Parteien regiert werden. Historisch unterschieden sich die wohlfahrtsstaatlichen Zielsetzungen von Christdemokraten und Sozialdemokraten deutlich. Können diese Parteiendifferenzen auch nach drei Jahrzehnten als gegeben vorausgesetzt werden, die durch einen Diskurs über die Notwendigkeiten wohlfahrtsstaatlicher Einschränkungen, der Anpassung und Modifizierung gekennzeichnet waren? In welcher Weise haben ?neue? Ideen die sozial- und wirtschaftspolitischen Konzepte der Parteien verändert? Unsere Hypothese ist, dass die Unterschiede zwischen den beiden Wohlfahrtsstaats-Parteien in ehemals konservativen Wohlfahrtsstaaten weitgehend abgeschmolzen sind. Zudem verfolgen sowohl Sozialdemokraten als auch Christdemokraten in diesen Ländern zunehmend einen liberal-kommunitaristischen Ansatz wohlfahrtsstaatlicher Politik. Die Studie basiert auf einer eingehenden Analyse der Programmatik von Sozialdemokraten und Christdemokraten in Österreich, Deutschland und den Niederlanden seit 1975. Ausgehend von christ- und sozialdemokratischen Idealtypen liegt der Fokus der Untersuchung auf Entwicklungen in den Feldern der Beschäftigungspolitik, der Politik der sozialen Sicherung sowie der Familienpolitik.
Keywords: 330; Sozialpolitik; Sozialstaat; Familienpolitik; Beschäftigungspolitik; Soziale Sicherung; Sozialdemokratische Partei; Konservative Partei; Österreich; Deutschland; Niederlande